Psychological distress is associated with pain and symptom severity in patients with longstanding hip and groin pain: A cross-sectional study - Anders Pålsson; Carl Bjerkelund; Andreas Ivarsson; Ioannis Kostogiannis; Eva Ageberg (JSAMS Plus)
Background: The primary aim was to assess psychological distress in patients with longstanding hip and groin pain (LHGP) and compare them with healthy controls. The secondary aim was to explore the association between psychological distress and symptom duration, self-reported pain and symptoms in patients with LHGP. Methods: Seventy-two patients with LHGP and sixty-three controls were included. The Kessler Psychological Distress Scale (K10) was used to assess psychological distress and the Copenhagen Hip and Groin Outcome Score (HAGOS) subscale for pain and symptoms to assess hip and groin pain and symptoms. The Mann–Whitney U test was used for between-group comparisons, and the Spearman's rank-order correlation to examine the association between the K10 and HAGOS. Results: There was no difference in psychological distress between patients with LHGP and controls (p ​= ​0.060) on the K10 total score. More individuals were categorized as having “high or very high” psychological distress in the LHGP group (45 ​%) compared to the control group (26 ​%) (p ​= ​0.035). There was no difference between patients with 3–12 months and >12 months symptom duration for the K10 (p ​= ​0.232). There was a moderate association between more psychological distress and worse self-reported pain (p ​= ​0.003) and symptoms (p ​< ​0.001). Conclusions: In this exploratory study, no difference was observed between patients and controls on the K10 total score; however, more patients with LHGP were categorized as having high or very high levels of psychological distress compared to controls. Among patients, symptom duration did not influence psychological distress, but a moderate association was found between more distress, greater pain, and more severe symptoms.